Lung function and home indoor exposure to PM10 among 7-12 years old children in rural area of Tumpat, Kelantan - Ismail, Zaliha (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2009)
INTRODUCTION: The co.n centration of in<!.o or particulate matter IO (PM10) was found much higher concentration than outside and it was important because most of people spend 80% of their time if'l.door. It was noted that PM10 has an impact on human health especially to the vulnerable group. It had significant negative effect on children lung function. The aim of this study was to determine the relationship between lung function and exposure to .. home indoor PM10 among 7-12 years old children in Mukim Simpangan, Tumpat, Kelantan. METHODOLOGY: A cross sectional study was ca:i:ied out in four villages in Mukim Simpangan, Jajahan Tumpat, Kelantan from April 2006 till August 2007. Total of 69 houses and 69 children were identified according to inclusion and exclusion criteria. This study was started with a session of interview assisted self-administered questionnaire to the selected house occupants based on ATS-DLD-78C questionnaire. Then, indoor PM10 level of each selected houses were measured for 24 hours using an aerosol monitor. Lung function test using portable spirometer was done for the child who lived in the house. RESULTS: All participants were Malay with mean (SD) age of 10.0 (I.SI) years. The mean of indoor PM10 level in this study was 104.0 (74.54) μg/m3 . Indoor activities such as cooking and usage of mosquito coil were identified as the significant factors that METHODOLOGY: A cross sectional study was ca:i:ied out in four villages in Mukim Simpangan, Jajahan Tumpat, Kelantan from April 2006 till August 2007. Total of 69 houses and 69 children were identified according to inclusion and exclusion criteria. This study was started with a session of interview assisted self-administered questionnaire to the selected house occupants based on ATS-DLD-78C questionnaire. Then, indoor PM10 level of each selected houses were measured for 24 hours using an aerosol monitor. Lung function test using portable spirometer was done for the child who lived in the house. RESULTS: All participants were Malay with mean (SD) age of 10.0 (I.SI) years. The mean of indoor PM10 level in this study was 104.0 (74.54) μg/m3 . Indoor activities such as cooking and usage of mosquito coil were identified as the significant factors that contributed to indoor PM10. Outdoor factors that have influenced in indoor PMio level were location of house from factory, main road and construction area; and frequency of heavy vehicle passed by the houses. Mean (SD) of children's lung function such .ll§. FEV i, FVC and ratio of FEV i/FVC ~ii' L6T (0.44) litre, 1.44 (0.39) litre and 86.33 (5.04) percent respectively. Indoor PM10 level, duration of child living in that area and total number of • • cigare.tte that smokeJ! arouncl and in the hou-il"e per day by the family members have negative association with at least one parameter of children's lung function. Father's levels ;Ji ·" "' of education and type of school transportation have positive association with at least one parameter of children's lung function. •. CONCLUSION: Indoor PMio level of 69 selected hquses in four villages in Mukim Simpangan, Turnpat, Kelantan was low and still acceptable to our Malaysian Ambient Air Quality Standard. Health programmes especially health promotion should be designed ' based on the factors that influenced the indoor air pollution and children's lung function.